RANCANG BANGUN SISTEM INFORMASI PENYIMPANAN ARSIP BERBASIS WEB DI JAKARTA - Nasril Nasril; M. Rizky Hidayah (JURNAL LENTERA ICT, 2023)
Archives are records of activities in various forms of media created and received by institutions in carrying out their activities. The process of securely storing information in the form of archives and organizing it neatly within a period of time determined by law is called archiving. Storing these archives is not easy, because archivists must record the location of the shelves where the boxes containing the archives will be placed. Based on the above explanation, the author is interested in creating an information system design for the archiving department, so the author has titled this final project “Designing a Web-Based Archive Storage Information System.” The purpose of this final project is to simplify the archive storage process to make it more effective. Before writing the final project, the author must follow a writing methodology, which includes searching for several references related to archives on the internet and conducting observations related to the archiving department. The conclusion of this final project is that the author can assist archivists in storing archives and can also present reports neatly and appropriately.